1998
DOI: 10.1007/pl00010772
|View full text |Cite
|
Sign up to set email alerts
|

Natural convection between coaxial vertical cylinders partially filled with a porous material

Abstract: This paper presents laminar fully developed free convection flow between two coaxial vertical cylinders partially filled with a porous matrix when the cylinders are kept at different temperatures. The Brinkman-extended Darcy model is used to simulate momentum transfer in the porous region. The two regions are coupled by equating the velocity and by considering shear stress jump condition at the interface. The effect of Darcy number on the velocity throughout porous domain and adjustable coefficient in the stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 10 publications
2
21
0
Order By: Relevance
“…Lawrence et al [4], Simon et al [5], Norbert et al [6] and Foreman et al [7] described rotating filters made of porous material with one or more rotors. Heat transfer in devices with porous material was studied by Mishra et al [8] and Paul et al [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lawrence et al [4], Simon et al [5], Norbert et al [6] and Foreman et al [7] described rotating filters made of porous material with one or more rotors. Heat transfer in devices with porous material was studied by Mishra et al [8] and Paul et al [9].…”
Section: Introductionmentioning
confidence: 99%
“…Open cell porous metal and ceramic materials can be used in numerous applications, such as filters [4][5][6][7], heat exchangers [8][9][10][11], air flow strengtheners, gas distributors [12], construction elements, energy absorbers, condensers, noise absorbers, burners, flame arrestors and also centrifugal rotors [13][14][15][16][17][18][19]. Lawrence et al [4], Simon et al [5], Norbert et al [6] and Foreman et al [7] described rotating filters made of porous material with one or more rotors.…”
Section: Introductionmentioning
confidence: 99%
“…Employing the Laplace transform technique (LTT), they have received the expression for the velocity, temperature, as well as skin friction. Free convection within two coaxial vertical cylinders partly loaded with porous corporeality has been inquired by Paul and Singh, 14 who observed that the velocity is influenced by the shear stress jump condition at the interface. The transient free convective flow within a vertical porous annulus has been handled by Jha et al 15 Using the perturbation technique, they have found the steady‐state solution for the velocity, temperature, skin friction, as well as the Nusselt number.…”
Section: Introductionmentioning
confidence: 99%
“…These boundary conditions are obtained by combining each of the two conditions having one boundary maintained at uniform heat flux or at uniform wall temperature with each of the conditions while the opposite boundary conditions is kept isothermal at the cove fluid temperature or adiabatic. Several authors (see Sastry et al(1987); Singh et al(1997); Paul et al(1998); Yan et al(2000)) have investigated the convective heat transfer in hydromagnetics in view of its utility in exploration, thermal recovery of oil and underground nuclear waste storage site. Sastry and Bhadram (1987) have considered the combined free and forced convective flow and heat transfer in vertical annulus when a radial magnetic field is applied.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al (1997) studied the fully developed natural convective flow in the presence of a radial magnetic field by obtaining a unified solution when the thermal boundary condition at the inner cylinder is of mixed kind while outer one is kept on constant temperature. Paul and Singh (1998) have shown the analytical solution of laminar fully developed free convective flow between two coaxial vertical cylinders partially filled with a porous medium and clear fluid. Yan (2000) has considered viscous flow about a submerged circular cylinder, with oscillates otherwise steady current.…”
Section: Introductionmentioning
confidence: 99%